Anthracene removal potential of green synthesized titanium dioxide nanoparticles (TiO2-NPs) and Alcaligenes faecalis HP8 from contaminated soil. (April 2023) - Chakravarty, Paramita; Deka, Hemen; Chowdhury, Devasish
Abstract: Anthracene biodegradation potential has been studied in liquid culture and soil microcosm environment by employing green synthesized TiO2 nanoparticles (NPs) and Alcaligenes faecalis HP8. The bacterium was isolated from crude oil contaminated soil, while TiO2 nanoparticles were synthesized using Paenibacillus sp. HD1PAH and Cyperus brevifolius which have PAHs remediation abilities. The dual application of TiO2 nanoparticles and Alcaligenes faecalis HP8 decreases anthracene concentration up to 21.3% in liquid at the end of 7 days and 37.9% in the soil treatments after completion of 30 days. Besides, the GC-MS analysis revealed production of five metabolites including 1, 2-anthracenedihydrodiol; 6, 7-benzocoumarin; 3-hydroxy-2-naphthoic acid; salicylic acid and 9, 10-anthraquinone at different time interval of the treatments. Anthracene degradation pathway confirms the breakdown of three ring anthracene to one ring salicylic acid. Additionally, soil dehydrogenase, urease, alkaline phosphatase, catalase and amylase activities increased up to 4.09 folds, 8.6 folds, 4.4 folds, 3.6 folds and 2.1 folds respectively after the combined treatments of TiO2 nanoparticles and Alcaligenes faecalis HP8. The bacterial biomass and residual anthracene concentration were found to be negatively correlated. Finally, the study brings into light a novel anthracene biodegradation pathway and provides a new dimension in nano assisted bacterial remediation. Graphical abstract: Image 1 Highlights: TiO2 nanoparticles with A lcaligenes faecalis HP8 showed higher anthracene reduction. Breakdown of three ringed anthracene to one ringed salicylic acid. Improvement in soil enzyme activities after the use of nano-bacteria combinations.